PHYSICO-CHEMICAL PARAMETERS AND PROTEOLYTIC POTENTIALS OF FUNGAL FLORA OF SOILS STRESSED BY TANNERY WASTES IN JOS, NIGERIA - Nwadiaro P. O.; Ogbonna A. I.; Moneme J. C.; Chuku A.; Makut M. D. (European Scientific Journal, ESJ, 2015)
The physico-chemical parameters and proteolytic potentials of fungal population in soils stressed by tannery wastes were investigated. The fungal species were isolated using hair baiting technique. Sabouraud Dextose Agar (SDA) medium was used for the isolation work. The pH, percentage moisture/organic matter contents and elemental analysis of the soil samples were assessed. The assessment of the soils polluted with tannery wastes was compared with that of the control sample collected from soils devoid of tannery activities. The results of the physico-chemical parameters of the soil samples showed the pH values of the soils to be 7.32, 7.53 and 6.46 for soils collected from Naraguta tannery (SNG), Dodo Street tannery (SDS) and College of Forestry, Jos (SCF control) respectively. The percentage moisture content values recorded for the soil samples from the two tanneries were higher than that of the control soil. The nitrogen level of the soil samples ranged from 0.010-0.19% while phosphorus ranged from 1.4-24mg/kg. The sodium levels were between 1.0-2.0mg/kg while the calcium levels ranged from 900-5080mg/kg. Twenty-one fungi species belonging to 12 genera were isolated from the experimental soil samples. Three of the genera including Cunninghamella elegans, Mucor haemalis and Rhizopus sp belong to the class phycomycetes. Others belong to the class hyphomycetes. Aspergillus niger had the highest number of isolation as well as highest frequencies of occurrence. Nine fungal species produced zones of clearance on the skim milk casein agar medium used for the assay of proteolytic activity indicating their potentials as keratin degraders.